2017
DOI: 10.1074/jbc.m117.789313
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70 interdomain linker is a dynamic switch that enables allosteric communication between two structured domains

Abstract: Hsp70 molecular chaperones play key roles in cellular protein homeostasis by binding to exposed hydrophobic regions of incompletely folded or aggregated proteins. This crucial Hsp70 function relies on allosteric communication between two well-structured domains: an N-terminal nucleotide-binding domain (NBD) and a C-terminal substrate-binding domain (SBD), which are tethered by an interdomain linker. ATP or ADP binding to the NBD alters the substrate-binding affinity of the SBD, triggering functionally essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 54 publications
2
62
1
3
Order By: Relevance
“…In our group we have studied allosterism in both directions: first, from the NBD to the SBD, studying BiP mechanical properties at the single molecule level with optical tweezer manipulation, and now in this work from the SBD to the NBD with ensemble measurements with nano‐rheological experimental setup. This study has shown that there exists a communication between both domains, as when peptide is bound in the SBD, the affinity for ADP bound in the NBD is modified (evidenced by the drop in K D value), demonstrating that SBD is allosterically coupled to NBD, as described in previous studies . This was expectable, considering that it was reported also that peptide binding accelerates BiP's ATPase activity .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our group we have studied allosterism in both directions: first, from the NBD to the SBD, studying BiP mechanical properties at the single molecule level with optical tweezer manipulation, and now in this work from the SBD to the NBD with ensemble measurements with nano‐rheological experimental setup. This study has shown that there exists a communication between both domains, as when peptide is bound in the SBD, the affinity for ADP bound in the NBD is modified (evidenced by the drop in K D value), demonstrating that SBD is allosterically coupled to NBD, as described in previous studies . This was expectable, considering that it was reported also that peptide binding accelerates BiP's ATPase activity .…”
Section: Discussionsupporting
confidence: 80%
“…This study has shown that there exists a communication between both domains, as when peptide is bound in the SBD, the affinity for ADP bound in the NBD is modified (evidenced by the drop in K D value), demonstrating that SBD is allosterically coupled to NBD, as described in previous studies. 30 This was expectable, considering that it was reported also that peptide binding accelerates BiP's ATPase activity. 31 However, it has not been tested before that the mechanical response of BiP upon ligand binding, can modulate the function of both binding domains particularly operating via changes in its internal viscosity.…”
Section: K D 'S Determination For Bip Nucleotides and Allosterism Betmentioning
confidence: 92%
“…Though no model for the mechanistic role of the D HPD -R NBD interaction per se has been previously put forth, the functional connection between these residues is well supported by genetic and biochemical data. Alteration of either R NBD or residues interacting with it (D SBD and D Lk ) 10, 11,14,17,34,38 disrupt allosteric communication between domains, resulting in a somewhat increased basal activity and ineffective stimulation by its JDP partner, DnaJ in the case of DnaK 14 and Hsc20 in the case of Ssc1 ( Supplementary Fig. S4).…”
Section: Discussionmentioning
confidence: 99%
“…A critical segment of this interface is formed by interactions at the base of the NBD with the linker and SBDb (called NBD/SBDb,linker throughout) 5,6, 13 . The linker plays an important role, as its interaction with the NBD is key to stimulation of ATPase activity [14][15][16][17] . A transient allosterically active intermediate poised for hydrolysis of ATP, often referred to as the "allosterically active state", has been observed in the presence of a peptide substrate -NBD/SBD contacts are largely absent, but the linker remains bound to the NBD 10, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The SBD and NBD remain attached through a short linker that has been implicated in modulating the domain interactions. In the ATP bound state, the linker has been observed to bind the NBD facilitating the docked conformation (2,3). Disruption of the NBD-linker interaction has been suggested to promote the undocked conformation associated with ATP-hydrolysis (4).…”
Section: Introductionmentioning
confidence: 99%